Use prospect of the of athermic technologies of metal softening for rolling stock elements - Vakulenko, I. A.; Proydak, S. V.; Grischenko, N. N. (Science and Transport Progress, 2013)
Purpose. The purpose of work is the possibility estimation of аthermic technologies use of cold-deformed metal softening for elements of railway car body and wheel. Methodology. The material for research is the carbon steel of the wheel rim fragment containing 0.55%С, 0.74%Mn, 0.33%Si, and the steel 20. The wheel steel is studied after heat strengthening and cold work after operation. Steel 20 is studied after plastic cold work by rolling. Electric pulse treatment (ET) is carried out on the special equipment. As the property of metal strength the Vickers hardness number is used. The microstructure research is carried out using the light and electronic microscope. Findings. During operation of the rolling stock elements with different strength level origin of damages on metallic surfaces is caused by a simultaneous load action. Taking into account that forming of breakdown sites is largely determined by the state of metal volumes nearby the places of maximal active voltages, the technology development of defect accumulation slowdown or the level of active voltages development allow one to prolong the operating term of rolling stock elements. After electric pulse treatment of the wheel rim fragment the regular changes of metal internal structure corresponded to the hardness changes. The hardness of low carbon steel increases proportional to the increase of the level of cold work by rolling. Alternating bending of the cold-deformed flat is accompanied by strength decrease, which is caused by the metal substructure changes. Originality. The softening process of the cold-worked steel is accompanied by substructure changes, which to a greater extent correspond to the hardening development from the plastic cold-work: dispersion of the dislocation cellular structure, formation of the new sub boundaries and displacement of the formed sub boundaries. Practical value. Introduction of electric pulse treatment in the conditions of railway depots repair base allow one to attain the required level of softening of the cold-worked steel on the wheel thread of railway wheel without heating of metal. The given treatment reduces the metal hardness and prolongs the term of incisors use during the renovation of the rolling profile of the railway wheel